Makna Simbolik Stupa di Depan Rumah Umat Buddha Vihara Mahanama: Kajian Antropologi dan Semiotika Arsitektur Buddhis - Susilo Susilo (Jurnal Budi Pekerti Agama Buddha, 2024)
This research aims to uncover the symbolic meaning of stupas placed in front of houses of Buddhist communities affiliated with Vihara Mahanama in Semanding Village, Central Java. Stupas as architectural and symbolic elements hold important positions in religious practice and cultural identity of local Buddhist communities. This study employs a qualitative approach using case study methods with ethnographic perspectives. Data collection techniques include field observations, in-depth interviews with Buddhist communities and vihara leaders, and visual documentation. Data were analyzed descriptively-interpretively using symbolic anthropology frameworks and semiotic architecture theory to reveal symbolic meanings contained in the form, placement, and social function of stupas in daily life. The results show that stupas are not merely religious ornaments, but represent multiple layers of meaning: spiritual values, cosmic symbolism, protection, and markers of Buddhist cultural identity in predominantly non-Buddhist environments. Stupa symbolism also reflects processes of cultural adaptation and spirituality rooted in the social dynamics of the Semanding Village community. This research contributes to understanding the integration of Buddhist symbols in contemporary Indonesian society and their role in maintaining religious identity in multicultural contexts, while also providing insights into the domestication of sacred symbols in everyday spaces.